A zinc oxide-based composite target material and its preparation method and application

By doping the impurity phases of aluminum oxide, other metal oxides and the first mixture into the zinc oxide matrix, the conductivity and density of the zinc oxide target are improved, and the problem of insufficient conductivity of the zinc oxide target in the prior art is solved, and a high-performance transparent conductive electrode suitable for the photovoltaic industry is realized.

CN118851743BActive Publication Date: 2025-03-21TRIO METAL (GZ) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411023228.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-03-21
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

The existing zinc oxide target preparation process is prone to introduce impurities, resulting in the conductivity of the photovoltaic industry that cannot meet the requirements of the photovoltaic industry.

Method used

Carrier concentration and conductivity are improved by doping the zinc oxide matrix with an impurity phase formed by alumina, other metal oxides, and the first mixture. Specific processes include mixed ball milling, drying, vacuum sintering, cold isostatic and hot press sintering.

Benefits of technology

It realizes the high conductivity and density of zinc oxide-based composite targets, reduces the impurity content, is suitable for transparent conductive electrodes in the photovoltaic industry, and has a simple process and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851743B_ABST
    Figure CN118851743B_ABST
Patent Text Reader

Abstract

The present invention discloses a zinc oxide-based composite target material and a preparation method and application thereof, belonging to the field of solar cell technology in the photovoltaic industry. Every 100 parts of the raw materials for preparing the composite target material include 0.8-1.2 parts of a first mixture, 0.8-1.5 parts of aluminum oxide, 0.4-0.8 parts of other metal oxides and 96.5-98 parts of zinc oxide; the first mixture includes yttrium oxide, barium carbonate and copper oxide in a ratio of 1:(1.8-2.2):(2.8-3.2); the metal in the other metal oxides is selected from at least one of gallium, indium and magnesium. The composite target material has high conductivity and density, low impurity content, and is suitable for transparent conductive electrodes in the photovoltaic industry. The preparation method thereof includes: subjecting the raw materials to first ball milling, drying, first vacuum sintering, second ball milling, cold isostatic pressing, second vacuum sintering and hot pressing sintering. The method is simple, easy to operate and can be industrialized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells in the photovoltaic industry, and in particular to a zinc oxide-based composite target material and a preparation method and application thereof. Background Art

[0002] Zinc oxide is a wide bandgap II-VI semiconductor material with advantages such as high melting point, low deposition temperature and low electron-induced defects. Zinc oxide target refers to a material with zinc oxide as the main component used in thin film deposition technologies such as physical vapor deposition.

[0003] The conductivity of zinc oxide targets has a direct impact on the performance of transparent conductive electrodes. The existing zinc oxide target preparation process usually adopts the slip casting method, such as preparing zinc oxide into a slurry and introducing it into a gypsum mold, and then preparing it through degreasing and high-temperature sintering. The zinc oxide targets prepared by this process are prone to introduce impurities, and the conductivity cannot meet the requirements of the photovoltaic industry. In addition, the conductivity of zinc oxide targets prepared by other methods also needs to be further improved.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a zinc oxide-based composite target material and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a zinc oxide-based composite target material, the zinc oxide-based composite target material comprising a zinc oxide matrix and an impurity phase doped in the zinc oxide matrix;

[0008] In terms of weight, every 100 parts of the raw materials for preparing the zinc oxide-based composite target material include 0.8 to 1.2 parts of the first mixture, 0.8 to 1.5 parts of aluminum oxide, 0.4 to 0.8 parts of other metal oxides, and 96.5 to 98 parts of zinc oxide;

[0009] The first mixture includes yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:(1.8-2.2):(2.8-3.2); the metal in other metal oxides is selected from at least one of gallium, indium and magnesium.

[0010] In an optional embodiment, every 100 parts of the preparation raw materials include 0.8 to 1.2 parts of the first mixture, 1 to 1.5 parts of aluminum oxide, 0.5 to 0.8 parts of other metal oxides, and 96.5 to 97.5 parts of zinc oxide.

[0011] In an optional embodiment, every 100 parts of the preparation raw materials include 1 part of the first mixture, 1 part of aluminum oxide, 0.5 parts of other metal oxides, and 97.5 parts of zinc oxide.

[0012] In an alternative embodiment, the first mixture includes yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:2:3.

[0013] In an optional embodiment, the zinc oxide-based composite target has at least one of the following characteristics:

[0014] Feature 1: The resistivity of zinc oxide-based composite target is ≤0.6mΩ·cm;

[0015] Feature 2: The density of zinc oxide-based composite target is ≥99.5%.

[0016] In a second aspect, the present invention provides a method for preparing a zinc oxide-based composite target material as described in any of the aforementioned embodiments, comprising the following steps: mixing the prepared raw materials, performing a first ball milling, drying, a first vacuum sintering, a second ball milling, cold isostatic pressing, a second vacuum sintering, and hot pressing sintering.

[0017] In an optional embodiment, the first ball milling includes at least one of the following features:

[0018] Feature 3: The speed of the first ball milling is 200r / min~1000r / min;

[0019] Feature 4: The first ball milling time is 4h to 24h;

[0020] Feature 5: The raw material is mixed with water and a first dispersant and then ball milled for the first time, wherein the mass of water is 1 to 3 times of the raw material, and the mass of the first dispersant is 2wt% to 10wt% of the raw material.

[0021] In an optional embodiment, drying includes at least one of the following features:

[0022] Feature 6: Drying method is spray drying;

[0023] Feature 7: Drying temperature is 100℃~300℃;

[0024] Feature 8: Drying pressure is 0.2MPa~0.8MPa;

[0025] Feature 9: Drying time is 30min to 180min.

[0026] In an optional embodiment, the first vacuum sintering includes at least one of the following features:

[0027] Feature 10: The temperature of the first vacuum sintering is 400℃~700℃;

[0028] Feature 11: The first vacuum sintering time is 2h to 10h.

[0029] In an optional embodiment, the second ball milling includes at least one of the following features:

[0030] Feature 12: The second ball milling is dry ball milling;

[0031] Feature 13: The ball-to-material ratio of the second ball milling is 1:1 to 3:1 by mass;

[0032] Feature 14: The speed of the second ball milling is 200r / min to 1000r / min;

[0033] Feature 15: The second ball milling time is 24h to 72h.

[0034] In an optional embodiment, the cold isostatic pressing includes at least one of the following features:

[0035] Feature 16: The pressure of cold isostatic pressing is 200MPa to 300MPa;

[0036] Feature 17: The cold isostatic pressing time is 10 min to 60 min;

[0037] Feature 18: The abrasive obtained from the second ball milling is mixed with a binder and then cold isostatically pressed, wherein the mass of the binder is 1wt% to 20wt% of the abrasive.

[0038] In an optional embodiment, the second vacuum sintering includes at least one of the following features:

[0039] Feature 19: The temperature of the second vacuum sintering is 400℃~600℃;

[0040] Feature 20: The time for the second vacuum sintering is 10h to 48h.

[0041] In an optional embodiment, hot pressing sintering includes at least one of the following features:

[0042] Feature 21: The temperature of hot pressing sintering is 850℃~950℃;

[0043] Feature 22: The pressure of hot pressing sintering is 100MPa to 200MPa;

[0044] Feature 23: The hot pressing sintering time is 2h to 24h;

[0045] Feature 24: During the hot pressing sintering process, the hot pressing sintering is carried out in an oxygen atmosphere during the first 80% to 95% of the insulation time, and the hot pressing sintering is carried out in a reducing atmosphere during the remaining time.

[0046] In an optional embodiment, the preparation of the first mixture in the raw material includes: mixing yttrium oxide, barium carbonate and copper oxide, and then performing wet ball milling, drying, degreasing, dry grinding and vacuum sintering.

[0047] In an optional embodiment, the wet ball milling in the first mixture preparation process includes at least one of the following features:

[0048] Feature 25: The rotation speed of wet ball milling is 200r / min to 1000r / min;

[0049] Feature 26: The wet ball milling time is 4h to 24h;

[0050] Feature 27: A mixture of yttrium oxide, barium carbonate and copper oxide is mixed with water and a second dispersant and then wet-milled, wherein the mass of water is 1 to 3 times the mass of the mixture, and the mass of the second dispersant is 2 wt% to 10 wt% of the mixture.

[0051] In an optional embodiment, the drying during the preparation of the first mixture includes at least one of the following features:

[0052] Feature 28: The drying method is spray drying;

[0053] Feature 29: Drying temperature is 100°C to 300°C;

[0054] Feature 30: Drying pressure is 0.2MPa to 0.8MPa;

[0055] Feature 31: Drying time is 30min to 180min.

[0056] In an optional embodiment, the defatting during the preparation of the first mixture includes at least one of the following features:

[0057] Feature 32: Degreasing temperature is 400℃~700℃;

[0058] Feature 33: The degreasing time is 2h to 10h.

[0059] In an optional embodiment, the dry grinding during the preparation of the first mixture includes at least one of the following features:

[0060] Feature 34: The ball-to-material ratio for dry grinding is 1:1 to 3:1 by mass;

[0061] Feature 35: The speed of dry grinding is 200r / min~1000r / min;

[0062] Feature 36: The dry grinding time is 24h to 72h.

[0063] In an optional embodiment, the vacuum sintering during the preparation of the first mixture includes at least one of the following features:

[0064] Feature 37: The vacuum sintering temperature is 900℃~950℃;

[0065] Feature 38: The vacuum sintering time is 12h to 24h.

[0066] In a third aspect, the present invention provides an application of a zinc oxide-based composite target material according to any one of the aforementioned embodiments, wherein the zinc oxide-based composite target material is used to prepare a transparent conductive electrode.

[0067] In a fourth aspect, the present invention provides a transparent conductive electrode, wherein the raw materials for preparing the transparent conductive electrode include the zinc oxide-based composite target material of any one of the aforementioned embodiments.

[0068] The beneficial effects of the present invention include:

[0069] The present invention forms an impurity phase doped in the zinc oxide matrix by aluminum oxide, other metal oxides and a first mixture. The impurity phase can increase the carrier concentration in the zinc oxide matrix and increase the conductivity. Moreover, if the total amount of the first mixture, aluminum oxide and other metal oxides is too high, the crystal structure of the zinc oxide matrix will be distorted and the cost advantage of the target material will be reduced. If the amount of the first mixed powder is too low, the amount of impurity phases will be insufficient, which is not conducive to the improvement of conductivity. If the amount of aluminum oxide or other metal oxides added is too little, the carrier concentration will not be sufficiently increased; if the amount of aluminum oxide or other metal oxides added is too high, it will be not conducive to cost control.

[0070] The zinc oxide-based composite target material provided by the present invention has low cost, high conductivity, and low impurity content, and is suitable for transparent conductive electrodes in the photovoltaic industry. The preparation method of the zinc oxide-based composite target material is simple, easy to operate, and can be industrially produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0072] Figure 1 This is the SEM image of the zinc oxide-based composite target prepared in Example 1. DETAILED DESCRIPTION

[0073] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0074] The zinc oxide-based composite target material provided by the present invention and its preparation method and application are described in detail below.

[0075] The zinc oxide-based composite target material provided by the present invention comprises a zinc oxide matrix and an impurity phase doped in the zinc oxide matrix.

[0076] In the present invention, every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 0.8 to 1.2 parts of the first mixture, 0.8 to 1.5 parts of aluminum oxide, 0.4 to 0.8 parts of other metal oxides and 96.5 to 98 parts of zinc oxide, by mass.

[0077] The first mixture is composed of yttrium oxide, barium carbonate and copper oxide, and the metal in other metal oxides is selected from at least one of gallium, indium and magnesium.

[0078] By doping the zinc oxide matrix with an impurity phase formed by aluminum oxide, other metal oxides, yttrium oxide, barium carbonate and copper oxide, the carrier concentration in the zinc oxide matrix can be increased, thereby increasing the conductivity.

[0079] The amount of the first mixture may be 0.8 parts, 0.85 parts, 0.9 parts, 0.95 parts, 1 parts, 1.05 parts, 1.1 parts, 1.15 parts or 1.2 parts, or any other value within the range of 0.8 parts to 1.2 parts.

[0080] The amount of aluminum oxide used can be 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts, etc., and can also be any other value within the range of 0.8 parts to 1.5 parts.

[0081] The amount of other metal oxides used can be 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts, etc., and can also be any other value within the range of 0.4 parts to 0.8 parts.

[0082] The amount of zinc oxide used can be 96.5 parts, 97 parts, 97.5 parts or 98 parts, etc., or any other value within the range of 96.5 parts to 98 parts.

[0083] If the proportion of doping raw materials (i.e., aluminum oxide, other metal oxides, and the first mixture) is too high, the crystal structure of the zinc oxide matrix will be distorted and the cost advantage of the target material will be reduced. If the amount of the first mixed powder is too low, the amount of impurity phase will be insufficient, which is not conducive to the improvement of conductivity. If the amount of aluminum oxide or other metal oxides added is too little, the carrier concentration will not be increased enough; if the amount of aluminum oxide or other metal oxides added is too high, it is easy to cause excessive distortion of the substrate crystal and is not conducive to cost control.

[0084] The first mixture includes yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:(1.8-2.2):(2.8-3.2).

[0085] The mass ratio of yttrium oxide to barium carbonate can be 1:1.8, 1:1.85, 1:1.9, 1:1.95, 1:2, 1:2.05, 1:2.1, 1:2.15 or 1:2.2, etc., or other values ​​within the range of 1:(1.8-2.2).

[0086] The mass ratio of yttrium oxide to copper oxide can be 1:2.8, 1:2.85, 1:2.9, 1:2.95, 1:3, 1:3.05, 1:3.1, 1:3.15 or 1:3.2, etc., or other values ​​within the range of 1:(2.8-3.2).

[0087] In some typical embodiments, every 100 parts of the preparation raw materials include 0.8 to 1.2 parts of the first mixture, 1 to 1.5 parts of aluminum oxide, 0.5 to 0.8 parts of other metal oxides, and 96.5 to 97.5 parts of zinc oxide.

[0088] In some more typical embodiments, every 100 parts of the preparation raw materials include 1 part of the first mixture, 1 part of aluminum oxide, 0.5 parts of other metal oxides and 97.5 parts of zinc oxide. The first mixture includes yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:2:3.

[0089] It should be noted that in the present invention, the first mixed powder prepared by co-preparing yttrium oxide, barium carbonate and copper oxide is mixed with aluminum oxide, other metal oxides and zinc oxide, rather than directly mixing yttrium oxide, barium carbonate, copper oxide with aluminum oxide, other metal oxides and zinc oxide at one time. This ensures that yttrium oxide, barium carbonate and copper oxide react first to form an intermediate phase and are not affected in the subsequent further preparation process with aluminum oxide, other metal oxides and zinc oxide. Mixing all the raw materials at the same time at one time is likely to lead to complex phases in the preparation process, and cannot more effectively improve the conductivity of the composite target material.

[0090] In some embodiments, the resistivity of the zinc oxide-based composite target is ≤0.6 mΩ·cm.

[0091] In some embodiments, the density of the zinc oxide-based composite target is ≥99.5.

[0092] In some embodiments, the impurity content of the zinc oxide-based composite target is ≤ 0.001%. “Impurities” refer to Fe, Ga, Cu, etc.

[0093] In line with the above, the zinc oxide-based composite target material provided by the present invention has high conductivity and density.

[0094] Low impurity content makes it suitable for transparent conductive electrodes in the photovoltaic industry.

[0095] Accordingly, the present invention provides a method for preparing the above-mentioned zinc oxide-based composite target material, comprising the following steps: mixing the preparation raw materials and then performing a first ball milling, drying, a first vacuum sintering, a second ball milling, cold isostatic pressing, a second vacuum sintering and hot pressing sintering.

[0096] In some embodiments, the raw materials can be mixed with water and a first dispersant before being subjected to a first ball milling, which is beneficial for grinding the materials finer.

[0097] The first ball milling can be carried out in an agate ball milling jar, and the material of the ball milling beads can be alumina. During the first ball milling process, the mass of water can be 1 to 3 times (such as 1 time, 1.5 times, 2 times, 2.5 times or 3 times, etc.) of the raw material, and the mass of the first dispersant can be 2wt% to 10wt% (such as 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc.) of the raw material. The above-mentioned first dispersant can be illustratively but not limitatively polyacrylic acid.

[0098] The rotation speed of the first ball milling can be 200 r / min to 1000 r / min, such as 200 r / min, 300 r / min, 500 r / min, 600 r / min, 700 r / min or 1000 r / min, or other values ​​within the range of 200 r / min to 1000 r / min.

[0099] The time of the first ball milling can be 4 h to 24 h, such as 4 h, 8 h, 12 h, 16 h, 20 h or 24 h, or other values ​​within the range of 4 h to 24 h.

[0100] In some embodiments, the drying method is spray drying. This method has a high drying efficiency, and during the spray drying process, the powders collide with each other under the action of high-pressure gas, which can obtain better sphericity and fluidity, which is conducive to improving the density in the subsequent pressing process.

[0101] The temperature of the spray drying can be 100°C to 300°C, such as 100°C, 150°C, 200°C, 250°C or 300°C, or other values ​​within the range of 100°C to 300°C. The pressure of the spray drying can be 0.2MPa to 0.8MPa, such as 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa or 0.8MPa, or other values ​​within the range of 0.2MPa to 0.8MPa. The time of the spray drying can be 30min to 180min, such as 30min, 60min, 90min, 120min, 150min or 180min, or other values ​​within the range of 30min to 180min.

[0102] In some embodiments, the mixed particle raw material obtained by spray drying can be placed in a corundum crucible in a glove box under argon protection and covered tightly, and then taken out and placed in a vacuum heating furnace for the first vacuum sintering. The temperature of the first vacuum sintering can be 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, or other values ​​within the range of 400°C to 700°C. The time of the first vacuum sintering can be 2h to 10h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, or other values ​​within the range of 2h to 10h.

[0103] The first vacuum sintering can remove organic dispersants such as polyacrylic acid used in the ball milling process.

[0104] In some embodiments, the second ball milling is dry ball milling, which can be more conducive to molding than wet ball milling. Before dry ball milling, the material obtained by the first vacuum sintering can be crushed. In terms of mass, the ball-to-material ratio of the second ball milling can be 1:1 to 3:1, such as 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, etc., or any other value within the range of 1:1 to 3:1. The rotation speed of the second ball milling can be 200r / min to 1000r / min, such as 200r / min, 300r / min, 500r / min, 600r / min, 700r / min or 1000r / min, etc., or other values ​​within the range of 200r / min to 1000r / min.

[0105] The time of the second ball milling can be 24 h to 72 h, such as 24 h, 36 h, 48 h, 60 h or 72 h, or other values ​​within the range of 24 h to 72 h.

[0106] In some embodiments, the ball milled material obtained by the second ball milling is first mixed with a binder and then cold isostatically pressed. For example, the ball milled raw material can be loaded into a powder mixer, and the binder can be sprayed in to fully mix. The mass of the binder is 1wt% to 20wt% of the ball milled material, such as 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%, etc., and can also be other values ​​within the range of 1wt% to 20wt%. The above-mentioned binder can be polyvinyl alcohol by way of example but not limitation.

[0107] The pressure of cold isostatic pressing can be 200MPa to 300MPa, such as 200MPa, 220MPa, 240MPa, 260MPa, 280MPa or 300MPa, etc., or other values ​​within the range of 200MPa to 300MPa. The time of cold isostatic pressing can be 10min to 60min, such as 10min, 20min, 30min, 40min, 50min or 60min, etc., or other values ​​within the range of 10min to 60min.

[0108] The density of the composite target can be improved by cold isostatic pressing.

[0109] In some embodiments, the temperature of the second vacuum sintering may be 400° C. to 600° C., such as 400° C., 450° C., 500° C., 550° C. or 600° C., or other values ​​within the range of 400° C. to 600° C. The time of the second vacuum sintering may be 10 h to 48 h, such as 10 h, 16 h, 22 h, 28 h, 34 h, 40 h or 48 h, or other values ​​within the range of 10 h to 48 h.

[0110] The second vacuum sintering can remove the binder used in the cold isostatic pressing and play a degreasing role.

[0111] In some embodiments, the temperature of hot pressing sintering can be 850°C to 950°C, such as 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C, etc., or other values ​​within the range of 850°C to 950°C. The pressure of hot pressing sintering can be 100MPa to 200MPa, such as 100MPa, 120MPa, 140MPa, 160MPa, 180MPa or 200MPa, etc., or other values ​​within the range of 100MPa to 200MPa. The time of hot pressing sintering can be 2h to 24h, such as 2h, 8h, 14h, 20h or 24h, etc., or other values ​​within the range of 2h to 24h.

[0112] During the hot pressing sintering process, the hot pressing sintering is performed in an oxygen atmosphere during the first 80% to 95% of the holding time, and in a reducing atmosphere during the remaining time, wherein the reducing atmosphere may be, for example but not limited to, a carbon monoxide atmosphere.

[0113] The hot pressing sintering mentioned above can promote grain growth and recrystallization, and improve density. If the temperature of hot pressing sintering is too high, it will cause the decomposition of the impurity phase; if the temperature of hot pressing sintering is too low, it will cause the material density to be low. The present invention can avoid the decomposition of the impurity phase and make the material have a higher density by applying pressure during the sintering process. In addition, by introducing oxygen in the early stage of hot pressing sintering, it can be ensured that the impurity phase will not lose oxygen and decompose. In the later stage of hot pressing sintering, a reducing atmosphere is used to appropriately increase the oxygen vacancies in the target material to improve the conductivity. However, if the reducing atmosphere time is too long, the target material will lose oxygen seriously and the composition will deviate from the design; if the reducing atmosphere time is too short, it will not be enough to form enough oxygen vacancies to improve the conductivity.

[0114] In the present invention, the preparation of the first mixture in the raw material may include: mixing yttrium oxide, barium carbonate and copper oxide and then performing wet ball milling, drying, degreasing, dry grinding and vacuum sintering.

[0115] In some embodiments, a mixture of yttrium oxide, barium carbonate and copper oxide can be mixed with water and a second dispersant and then wet ball milled, wherein the mass of water is 1 to 3 times (such as 1, 1.5, 2, 2.5 or 3 times) of the mixture, and the mass of the second dispersant is 2 wt% to 10 wt% (such as 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt% of the mixture). Similarly, the second dispersant can be illustratively but not limitatively polyacrylic acid.

[0116] The rotation speed of wet ball milling in the preparation process of the first mixture can be 200r / min to 1000r / min, such as 200r / min, 300r / min, 500r / min, 600r / min, 700r / min or 1000r / min, or other values ​​within the range of 200r / min to 1000r / min.

[0117] The time of wet ball milling can be 4 h to 24 h, such as 4 h, 8 h, 12 h, 16 h, 20 h or 24 h, etc., or other values ​​within the range of 4 h to 24 h.

[0118] The drying in the preparation process of the first mixture is also spray drying. The drying temperature can be 100°C to 300°C, such as 100°C, 150°C, 200°C, 250°C or 300°C, etc., or other values ​​within the range of 100°C to 300°C. The drying pressure can be 0.2MPa to 0.8MPa, such as 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa or 0.8MPa, etc., or other values ​​within the range of 0.2MPa to 0.8MPa. The drying time can be 30min to 180min, such as 30min, 60min, 90min, 120min, 150min or 180min, etc., or other values ​​within the range of 30min to 180min.

[0119] Further, the mixed particle raw material obtained by spray drying is placed in a corundum crucible in a glove box under argon protection and covered tightly, and then taken out and placed in a vacuum heating furnace for degreasing. The degreasing temperature can be 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, etc., or other values ​​within the range of 400°C to 700°C. The degreasing time can be 2h to 10h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc., or other values ​​within the range of 2h to 10h.

[0120] The ball-to-material ratio in dry grinding during the preparation of the first mixture can be 1:1 to 3:1 by mass, such as 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, or any other value within the range of 1:1 to 3:1.

[0121] The rotation speed of dry grinding can be 200r / min to 1000r / min, such as 200r / min, 300r / min, 500r / min, 600r / min, 700r / min, 900r / min or 1000r / min, or other values ​​within the range of 200r / min to 1000r / min.

[0122] The dry grinding time can be 24 hours to 72 hours, such as 24 hours, 36 hours, 48 ​​hours, 60 hours or 72 hours, or other values ​​within the range of 24 hours to 72 hours.

[0123] The vacuum sintering temperature during the preparation of the first mixture may be 900° C. to 950° C., such as 900° C., 905° C., 910° C., 915° C., 920° C., 925° C., 930° C., 935° C., 940° C., 945° C. or 950° C., or other values ​​within the range of 900° C. to 950° C. The vacuum sintering time may be 12 h to 24 h, such as 12 h, 14 h, 16 h, 18 h, 20 h or 24 h, or other values ​​within the range of 12 h to 24 h.

[0124] As mentioned above, the zinc oxide-based composite target material prepared by the preparation method provided by the present invention can have high conductivity and high density at the same time, and the cost is also low.

[0125] In addition, the present invention also provides an application of the zinc oxide-based composite target material. For example, the zinc oxide-based composite target material can be used to prepare a transparent conductive electrode.

[0126] Correspondingly, the present invention also provides a transparent conductive electrode, the raw materials for preparing the transparent conductive electrode include the above-mentioned zinc oxide-based composite target material.

[0127] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0128] Example 1

[0129] This embodiment provides a zinc oxide-based composite target (such as Figure 1 As shown), the preparation method thereof comprises:

[0130] S1: preparing a first mixture.

[0131] S11: 120 g of yttrium oxide, barium carbonate and copper oxide were prepared in a mass ratio of 1:2:3 and loaded into an agate ball mill. The mixture was ball milled with alumina beads, and 150 mL of pure water and 3 g of polyacrylic acid were added. The mixture was wet milled at 800 r / min for 20 h.

[0132] S12: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.3 MPa for 60 min.

[0133] S13: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for degreasing. The degreasing temperature is 500° C. and the degreasing time is 6 hours.

[0134] S14: The defatted raw materials are crushed and then dry-milled again. The ball-to-material ratio in the dry-milling process is 3:1, the ball-milling time is 48 hours, and the rotation speed is 800 r / min.

[0135] S15: The dry-ground mixed powder is placed in a vacuum sintering furnace, heated to 920° C., kept warm for 12 hours, and then ground for later use.

[0136] S2: Preparation of zinc oxide based composite target.

[0137] S21: Prepare 1000 g of raw material by taking the first mixture powder, aluminum oxide, gallium oxide and zinc oxide in a mass ratio of 1:1.5:0.5:97. Put the mixed raw materials into an agate ball mill and perform wet ball milling with aluminum oxide grinding beads. During the wet ball milling process, add 1500 mL of pure water and 50 g of polyacrylic acid, and ball mill at a speed of 800 r / min for 24 hours.

[0138] S22: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.3 MPa for 60 min.

[0139] S23: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for the first vacuum sintering. The temperature of the first vacuum sintering is 500° C. and the time is 8 hours.

[0140] S24: The raw material obtained by the first vacuum sintering is crushed and then ball-milled for the second time. The second ball-milling is dry milling, the ball-to-material ratio is 2:1, the ball-milling speed is 800 r / min, and the ball-milling time is 72 h.

[0141] S25: The ball-milled raw material is loaded into a powder mixer, 55 g of polyvinyl alcohol solution (the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 20%) is sprayed into the powder mixer, and the mixed raw material is fully mixed. The mixed raw material is loaded into a special mold and then cold isostatically pressed at a pressure of 200 MPa for 30 minutes.

[0142] S26: placing the target blank after cold isostatic pressing into a vacuum heating furnace for a second vacuum sintering. The temperature of the second vacuum sintering is 550° C. and the time is 48 hours.

[0143] S27: Put the target blank after the second vacuum sintering into an atmosphere hot pressing furnace for hot pressing sintering. The hot pressing sintering temperature is 940°C, the pressure is 150MPa, and the time is 6h. During the hot pressing sintering process, the oxygen atmosphere is passed for the first 90% of the time, and the reducing atmosphere (CO atmosphere) is passed for the last 10% of the time.

[0144] Example 2

[0145] The difference between this embodiment and embodiment 1 is that:

[0146] S21: Take the first mixture powder, aluminum oxide, gallium oxide and zinc oxide in a mass ratio of 0.8:1.5:0.6:97.1 to prepare 1000g of raw materials. Put the mixed raw materials into an agate ball mill and perform wet ball milling with aluminum oxide grinding beads. During the wet ball milling process, add 1000mL of pure water and 20g of polyacrylic acid, and ball mill at a speed of 500r / min for 12h.

[0147] S22: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.2 MPa for 180 min.

[0148] S23: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for the first vacuum sintering. The temperature of the first vacuum sintering is 400° C. and the time is 10 hours.

[0149] S24: The raw material obtained by the first vacuum sintering is crushed and then ball-milled for the second time. The second ball-milling is dry milling, the ball-to-material ratio is 1:1, the ball-milling speed is 500 r / min, and the ball-milling time is 48 h.

[0150] S25: The ball-milled raw material is loaded into a powder mixer, 100 g of polyvinyl alcohol solution (the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 20%) is sprayed into the mixture, and the mixture is fully mixed. The mixed raw material is loaded into a special mold and cold isostatically pressed at a pressure of 250 MPa for 60 minutes.

[0151] S26: placing the target blank after cold isostatic pressing into a vacuum heating furnace for a second vacuum sintering. The temperature of the second vacuum sintering is 400° C. and the time is 24 hours.

[0152] S27: Put the target blank after the second vacuum sintering into an atmosphere hot pressing furnace for hot pressing sintering. The hot pressing sintering temperature is 850°C, the pressure is 100MPa, and the time is 24h. During the hot pressing sintering process, the oxygen atmosphere is passed for the first 80% of the time, and the reducing atmosphere (CO atmosphere) is passed for the last 20% of the time.

[0153] Example 3

[0154] The difference between this embodiment and embodiment 1 is that:

[0155] S21: Prepare 1000g of raw material by mixing the first mixture powder, aluminum oxide, gallium oxide and zinc oxide in a mass ratio of 1.2:1.5:0.8:96.5. Put the mixed raw materials into an agate ball mill and perform wet ball milling with aluminum oxide grinding beads. During the wet ball milling process, add 3000mL of pure water and 100g of polyacrylic acid, and ball mill at a speed of 700r / min for 4h.

[0156] S22: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.8 MPa for 30 min.

[0157] S23: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for the first vacuum sintering. The temperature of the first vacuum sintering is 700° C. and the time is 2 h.

[0158] S24: The raw materials obtained by the first vacuum sintering are crushed and then ball-milled for the second time. The second ball-milling is dry milling, the ball-to-material ratio is 3:1, the ball-milling speed is 700 r / min, and the ball-milling time is 24 h.

[0159] S25: The ball-milled raw material is loaded into a powder mixer, 100 g of polyvinyl alcohol solution (the mass fraction of polyvinyl alcohol in the polyvinyl alcohol solution is 25%) is sprayed into the mixture, and the mixture is fully mixed. The mixed raw material is loaded into a special mold and cold isostatically pressed at a pressure of 300 MPa for 10 minutes.

[0160] S26: placing the target blank after cold isostatic pressing into a vacuum heating furnace for a second vacuum sintering. The temperature of the second vacuum sintering is 600° C. and the time is 10 hours.

[0161] S27: Put the target blank after the second vacuum sintering into an atmosphere hot pressing furnace for hot pressing sintering. The hot pressing sintering temperature is 950°C, the pressure is 200MPa, and the time is 2h. During the hot pressing sintering process, the oxygen atmosphere is passed for the first 95% of the time, and the reducing atmosphere (CO atmosphere) is passed for the last 5% of the time.

[0162] Example 4

[0163] The difference between this embodiment and embodiment 1 is that:

[0164] S1: preparing a first mixture.

[0165] S11: 120 g of yttrium oxide, barium carbonate and copper oxide were prepared in a mass ratio of 1:1.8:3.2 and loaded into an agate ball mill. The mixture was ball milled with alumina grinding beads, and 120 mL of pure water and 2.4 g of polyacrylic acid were added, and wet ball milling was performed at 500 r / min for 24 h.

[0166] S12: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.2 MPa for 180 min.

[0167] S13: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for degreasing. The degreasing temperature is 400° C. and the degreasing time is 10 h.

[0168] S14: The defatted raw materials are crushed and then dry-milled again. The ball-to-material ratio in the dry-milling process is 1:1, the ball-milling time is 72 hours, and the rotation speed is 1000 r / min.

[0169] S15: The dry-ground mixed powder is placed in a vacuum sintering furnace, heated to 900° C., kept warm for 24 hours, and then ground for later use.

[0170] Example 5

[0171] The difference between this embodiment and embodiment 1 is that:

[0172] S1: preparing a first mixture.

[0173] S11: 120 g of yttrium oxide, barium carbonate and copper oxide were prepared in a mass ratio of 1:2.2:2.8 and loaded into an agate ball mill. The mixture was ball milled with alumina grinding beads, and 360 mL of pure water and 12 g of polyacrylic acid were added, and wet ball milling was performed at 800 r / min for 4 h.

[0174] S12: The ball-milled raw material is dried by spray drying at a temperature of 250° C. and a pressure of 0.8 MPa for 30 min.

[0175] S13: The dried mixed particle raw material is placed into a corundum crucible in a glove box under argon protection and covered tightly. After being taken out, it is placed in a vacuum heating furnace for degreasing. The degreasing temperature is 700° C. and the degreasing time is 2 h.

[0176] S14: The defatted raw materials are crushed and then dry-milled again. The ball-to-material ratio during the dry-milling process is 2:1, the ball-milling time is 24 hours, and the rotation speed is 500 r / min.

[0177] S15: The dry-ground mixed powder is placed in a vacuum sintering furnace, heated to 950° C., kept warm for 14 hours, and then ground for later use.

[0178] Example 6

[0179] The difference between this embodiment and embodiment 1 is that in S21, the mass ratio of the first mixture powder, aluminum oxide, gallium oxide and zinc oxide is 1:1:0.5:97.5.

[0180] Example 7

[0181] The difference between this embodiment and embodiment 1 is that an equal amount of gallium oxide is replaced by indium oxide.

[0182] Example 8

[0183] The difference between this embodiment and embodiment 1 is that an equal amount of gallium oxide is replaced by magnesium oxide.

[0184] Comparative Example 1

[0185] The difference between this comparative example and Example 1 is that the raw material for preparing the zinc oxide-based composite target does not contain the first mixture.

[0186] Comparative Example 2

[0187] The difference between this comparative example and Example 1 is that the raw materials for preparing the zinc oxide-based composite target material do not contain gallium oxide and aluminum oxide.

[0188] Comparative Example 3

[0189] The difference between this comparative example and Example 1 is that every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 1 part of yttrium oxide, 1.5 parts of aluminum oxide, 0.5 parts of gallium oxide and 97 parts of zinc oxide.

[0190] That is, the preparation raw materials do not contain barium carbonate and copper oxide.

[0191] Comparative Example 4

[0192] The difference between this comparative example and Example 1 is that every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 0.5 parts of the first mixture, 1.5 parts of aluminum oxide, 0.5 parts of gallium oxide and 97.5 parts of zinc oxide.

[0193] That is, the amount of the first mixture used in preparing the raw materials is reduced.

[0194] Comparative Example 5

[0195] The difference between this comparative example and Example 1 is that every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 2 parts of the first mixture, 1.5 parts of aluminum oxide, 0.5 parts of gallium oxide and 96 parts of zinc oxide.

[0196] That is, the amount of the first mixture used in preparing the raw material is increased.

[0197] Comparative Example 6

[0198] The difference between this comparative example and Example 1 is that every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 1 part of the first mixture, 4 parts of aluminum oxide, 0.5 parts of gallium oxide and 94.5 parts of zinc oxide.

[0199] That is, increase the amount of alumina in the preparation raw materials.

[0200] Comparative Example 7

[0201] The difference between this comparative example and Example 1 is that an equal amount of gallium oxide in the preparation raw material is replaced by titanium oxide.

[0202] Comparative Example 8

[0203] The difference between this comparative example and Example 1 is that the first mixture is not prepared first, but all the preparation raw materials are directly mixed at one time to prepare the zinc oxide-based composite target.

[0204] Comparative Example 9

[0205] The difference between this comparative example and Example 1 is that the temperature of the hot pressing sintering in S27 is 800°C.

[0206] Comparative Example 10

[0207] The difference between this comparative example and Example 1 is that the temperature of the hot pressing sintering in S27 is 1000°C.

[0208] Comparative Example 11

[0209] The difference between this comparative example and Example 1 is that no pressure is applied during the sintering process in S27, that is, the sintering process in S27 is carried out under normal pressure.

[0210] Comparative Example 12

[0211] The difference between this comparative example and Example 1 is that the hot pressing sintering in S27 is always carried out under oxygen-permeable conditions, and no reducing atmosphere is used in the later stage.

[0212] Test example

[0213] The zinc oxide-based composite targets prepared in Examples 1 to 8 and Comparative Examples 1 to 12 were subjected to performance tests, and the results are shown in Table 1.

[0214] Among them, the resistivity is tested by four-probe test and the density is tested by drainage method.

[0215] Table 1 Test results

[0216]

[0217]

[0218] It can be seen from Table 1 that the zinc oxide-based composite target materials prepared in Examples 1 to 8 of the present invention have higher conductivity and density.

[0219] By comparing Examples 1 to 6, it can be seen that the zinc oxide-based composite target prepared in Example 6 is overall superior in conductivity and density, indicating that the material ratio and process conditions provided in Example 6 are more suitable for preparing a zinc oxide-based composite target with better performance.

[0220] By comparing Example 1 and Comparative Examples 1 to 3, it can be seen that reducing the types of raw materials used in preparation will reduce the conductivity of the zinc oxide-based composite target.

[0221] By comparing Example 1 and Comparative Examples 4 to 6, it can be seen that when the amount of the raw materials used in the preparation is inappropriate, the conductivity of the zinc oxide-based composite target material will also be significantly deteriorated.

[0222] By comparing Example 1 and Comparative Example 7, it can be seen that when the raw materials are not properly selected, the conductivity of the zinc oxide-based composite target material may also deteriorate.

[0223] By comparing Example 1 and Comparative Examples 8 to 12, it can be seen that the preparation method and preparation conditions will also affect the conductivity or density of the zinc oxide-based composite target. If the preparation method or preparation conditions are inappropriate, a zinc oxide-based composite target having both high conductivity and density cannot be obtained.

[0224] In summary, the zinc oxide-based composite target provided by the present invention has high conductivity and density, low impurity content, and is suitable for transparent conductive electrodes in the photovoltaic industry. In addition, the preparation method of the zinc oxide-based composite target is simple, easy to operate, and can be industrially produced.

[0225] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A zinc oxide-based composite target, characterized in that: The zinc oxide-based composite target material comprises a zinc oxide matrix and an impurity phase doped in the zinc oxide matrix; In terms of mass, every 100 parts of raw materials for preparing the zinc oxide-based composite target material include 0.8 to 1.2 parts of the first mixture, 0.8 to 1.5 parts of aluminum oxide, 0.4 to 0.8 parts of other metal oxides, and 96.5 to 98 parts of zinc oxide; The first mixture comprises yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:(1.8-2.2):(2.8-3.2); the metal in the other metal oxide is selected from at least one of gallium, indium and magnesium; The preparation of the zinc oxide-based composite target material comprises the following steps: mixing the raw materials for preparation, performing a first ball milling, drying, a first vacuum sintering, a second ball milling, cold isostatic pressing, a second vacuum sintering and hot pressing sintering; The mixing of the raw materials includes: preparing a first mixed powder from yttrium oxide, barium carbonate and copper oxide, and then mixing it with aluminum oxide, other metal oxides and zinc oxide; During the hot pressing sintering process, the hot pressing sintering is carried out in an oxygen atmosphere during the first 80% to 95% of the holding time, and in a reducing atmosphere during the remaining time; the hot pressing sintering temperature is 850°C to 950°C; the hot pressing sintering pressure is 100MPa to 200MPa; and the hot pressing sintering time is 2h to 24h.

2. The zinc oxide-based composite target according to claim 1, characterized in that: Every 100 parts of the preparation raw materials include 0.8 to 1.2 parts of the first mixture, 1 to 1.5 parts of the aluminum oxide, 0.5 to 0.8 parts of the other metal oxides and 96.5 to 97.5 parts of the zinc oxide.

3. The zinc oxide-based composite target according to claim 2, characterized in that: Every 100 parts of the preparation raw materials include 1 part of the first mixture, 1 part of the aluminum oxide, 0.5 parts of the other metal oxides and 97.5 parts of the zinc oxide.

4. The zinc oxide-based composite target according to any one of claims 1 to 3, characterized in that: The first mixture includes yttrium oxide, barium carbonate and copper oxide in a mass ratio of 1:2:

3.

5. A method for preparing a zinc oxide-based composite target material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the prepared raw materials, performing the first ball milling, drying, the first vacuum sintering, the second ball milling, cold isostatic pressing, the second vacuum sintering and hot pressing sintering; The mixing of the raw materials includes: preparing a first mixed powder from yttrium oxide, barium carbonate and copper oxide, and then mixing it with aluminum oxide, other metal oxides and zinc oxide; During the hot pressing sintering process, the hot pressing sintering is carried out in an oxygen atmosphere during the first 80% to 95% of the holding time, and in a reducing atmosphere during the remaining time; the hot pressing sintering temperature is 850°C to 950°C; the hot pressing sintering pressure is 100MPa to 200MPa; and the hot pressing sintering time is 2h to 24h.

6. The preparation method according to claim 5, characterized in that: The first ball milling includes at least one of the following conditions: The speed of the first ball milling is 200r / min~1000r / min; The first ball milling time is 4h~24h; The raw material is mixed with water and a first dispersant and then ball-milled for the first time, wherein the mass of water is 1 to 3 times of the raw material, and the mass of the first dispersant is 2 wt% to 10 wt% of the raw material; and / or, Drying includes at least one of the following conditions: The drying method is spray drying; Drying temperature is 100℃~300℃; Drying pressure is 0.2MPa~0.8MPa; Drying time is 30min~180min; and / or, The temperature of the first vacuum sintering is 400℃~700℃; and / or, The second ball milling includes at least one of the following conditions: The second ball milling is dry ball milling; The ball-to-material ratio of the second ball milling is 1:1 to 3:1 by mass; The speed of the second ball milling is 200r / min~1000r / min; The second ball milling time is 24h~72h; and / or, Cold isostatic pressing includes at least one of the following conditions: The pressure of cold isostatic pressing is 200MPa~300MPa; The cold isostatic pressing time is 10min~60min; The abrasive obtained by the second ball milling is mixed with a binder and then cold isostatically pressed, wherein the mass of the binder is 1wt% to 20wt% of the abrasive; and / or, The second vacuum sintering includes at least one of the following conditions: The temperature of the second vacuum sintering is 400℃~600℃; The second vacuum sintering time is 10h~48h.

7. The preparation method according to claim 5, characterized in that: The preparation of the first mixture in the raw material preparation comprises: mixing yttrium oxide, barium carbonate and copper oxide and then performing wet ball milling, drying, degreasing, dry grinding and vacuum sintering.

8. The preparation method according to claim 7, characterized in that: The wet ball milling in the preparation process of the first mixture includes at least one of the following conditions: The speed of wet ball milling is 200r / min~1000r / min; The time for wet ball milling is 4h~24h; A mixture of yttrium oxide, barium carbonate and copper oxide is mixed with water and a second dispersant and then wet-milled, wherein the mass of water is 1 to 3 times of the mixture, and the mass of the second dispersant is 2 wt% to 10 wt% of the mixture; and / or, The drying during the preparation of the first mixture includes at least one of the following conditions: The drying method is spray drying; Drying temperature is 100℃~300℃; Drying pressure is 0.2MPa~0.8MPa; Drying time is 30min~180min; and / or, The degreasing during the preparation of the first mixture includes at least one of the following conditions: Degreasing temperature is 400℃~700℃; Degreasing time is 2h~10h; and / or, The dry grinding during the preparation of the first mixture includes at least one of the following conditions: The ball-to-material ratio for dry grinding is 1:1 to 3:1 by mass; The speed of dry grinding is 200r / min~1000r / min; The dry grinding time is 24h~72h; and / or, The vacuum sintering during the preparation of the first mixture includes at least one of the following conditions: The temperature of vacuum sintering is 900℃~950℃; The vacuum sintering time is 12h~24h.

9. An application of the zinc oxide-based composite target material according to any one of claims 1 to 4, characterized in that: The zinc oxide-based composite target material is used to prepare a transparent conductive electrode.

10. A transparent conductive electrode, characterized in that: The raw material for preparing the transparent conductive electrode includes the zinc oxide-based composite target material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Yttrium-doped AZO target material and preparation method thereof

    CN101580384A

  • Magnesium-doped zinc oxide magnetron sputtering target material and preparation method thereof

    CN112725752A

  • Superconducting target material and preparation method and application thereof

    CN114105631A